Kounis Syndrome together with Myocardial Bridging Leading to Acute Myocardial Infarction at Young Age - Ilker Murat Caglar; Alper Vural; Fatma Nihan Turhan Caglar; Murat Ugurlucan; Osman Karakaya (Case Reports in Medicine)
Kounis syndrome, also named as “allergic angina syndrome,” is a diagnosis in which exposure to an allergen causes mostly coronary spasm and rarely plaque rupture, resulting in ischemic myocardial events. Myocardial bridging is defined as an intramural segment of a coronary artery and its systolic compression by overlying fibers. Myocardial bridging generally has a benign prognosis and mostly affects the mid portion of left anterior descending coronary artery. However, some cases with myocardial ischemia, infarction, and sudden death have also been reported. A 17-year-old boy presented to the clinic with acute anterolateral myocardial infarction after having first dose of clindamycin and diagnosed as Kounis syndrome. Further diagnostic workup of the patient showed myocardial bridging at the mid left anterior descending artery. In this report, we present the combination of Kounis syndrome and myocardial bridging leading to myocardial infarction at young age.